Training for Reducing Academic Procrastination among University Students in Indonesia: A Literature Review - Putranto, Teguh Dwi; Prasetyo, Dwi (Proceedings of The International Conference on Psychology and Education, 2025)
Background: Academic procrastination experienced by university students not only hinders their plans to work immediately after graduation. If not handled immediately, academic procrastination can trigger serious problems, such as mental health problems in university students. This condition is certainly an obstacle that needs to be resolved so that it does not become a problem in the academic realm. Objective: To find out training to reduce academic procrastination among university students in Indonesia. Methods: This study uses a qualitative approach with the Literature Review method. The unit of analysis in this study is journal articles collected through a search process on "Garuda (http://garuda.kemdikbud.go.id/)" by entering the keyword "Student academic procrastination training." The articles used were those published in 2010 - 2025. Results: Researchers have obtained 8 articles from search results with the keywords "Student academic procrastination training". All eight articles were used in this research. Several forms of interventions have been used in previous studies to reduce academic procrastination. These interventions include self-management training, achievement motivation training, prayer training, self-regulation training, and problem-focused coping training. Conclusion: It was found that academic procrastination can be reduced through structured interventions such as 1) Achievement motivation training, 2) Self-regulated learning, and 3) Self-management. Self-management training is recommended towards the end of the semester (generally during the tenth to fourteenth week). This training is appropriate for students who are facing a major assignment such as a final report, thesis, or exam.